Human Resource Management In Corruption Prevention: A Systematic Review - Fazriyani, Fanesha; Prahyawan, Wawan (STIE Ekuitas, 2025)
Introduction/Main Objectives: This study aims to identify how human resource management policies and practices can be used to prevent and eradicate corruption in organizations in a particular country. Background Problems: Corruption remains a serious and widespread issue worldwide. It hinders economic development, erodes public trust, and weakens organizational and institutional integrity. The 2023 Corruption Perception Index highlights major disparities between countries, with Denmark ranked as the least corrupt and Somalia as the most corrupt. These differences emphasize the need for effective anti-corruption strategies, particularly in nations with fragile governance systems. Despite this urgency, HRM is often underutilized as a tool in addressing corruption. Novelty: This study offers a fresh perspective by framing HRM not just as an administrative support system, but as a central player in building ethical behavior and reducing corruption risks. It departs from the dominant legal and institutional focus in existing literature by emphasizing internal, human-centric approaches such as organizational culture and values. Research Methods: The study employs a systematic literature review method. It identifies, analyzes, and synthesizes academic research that explores how HRM practices—such as ethics training, awareness programs, and value-based leadership can contribute to corruption prevention. Finding/Results: The review shows that HRM practices, when integrated with ethics-oriented initiatives, can help organizations develop internal mechanisms that promote accountability, ethical decision-making, and a strong culture of integrity. Conclusion: Incorporating anti-corruption principles into HRM policies is a sustainable and strategic approach. Ethical HR practices not only strengthen organizational culture but also contribute to national anti-corruption goals and broader social welfare.